2016
DOI: 10.1161/atvbaha.116.308034
|View full text |Cite
|
Sign up to set email alerts
|

Probucol in Albuminuric Type 2 Diabetes Mellitus Patients on Renin–Angiotensin System Blockade

Abstract: Objective-To determine the effect of probucol on urine albumin excretion in type 2 diabetes mellitus patients with albuminuria using angiotensin-converting enzyme inhibitors or angiotensin receptor blockers. Approach and Results-This was a 16-week, phase II, randomized, placebo-controlled, parallel-group study in type 2 diabetes mellitus patients with a urinary albumin/creatinine ratio of ≥300 mg/g using angiotensin-converting enzyme inhibitors or angiotensin receptor blockers, conducted in 17 tertiary referra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Accurately monitoring early decreases in GFR is especially important in patients with diabetes because of their increased risk for kidney damage. Thus, several clinical trials use cystatin C as a secondary biomarker for renal function in diabetic populations …”
Section: Cystatin C For Staging Chronic Kidney Diseasementioning
confidence: 99%
“…Accurately monitoring early decreases in GFR is especially important in patients with diabetes because of their increased risk for kidney damage. Thus, several clinical trials use cystatin C as a secondary biomarker for renal function in diabetic populations …”
Section: Cystatin C For Staging Chronic Kidney Diseasementioning
confidence: 99%
“…Many studies have demonstrated that oxidative stress plays an important role in DN. Therefore, various clinical trials for therapeutic agents regulating oxidative stress are continuously being conducted (Table 1) [70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89]. Although no effective therapy exists for treatment of DN, clinical trials for therapeutic Nox inhibitors are ongoing [88,89].…”
Section: Development Of Nox Inhibitors For Treatment Of Diabetic Neph...mentioning
confidence: 99%
“…These authors reported that although probucol treatment resulted in significantly lowered total cholesterol and low density lipoprotein (LDL) cholesterol levels, no reduction in urinary albumin excretion was observed. However, it is to be noted that the majority of the subjects were already on statin therapy 55 .…”
Section: Studies In Human Subjectsmentioning
confidence: 99%